(untitled) (Bangladesh Medical Journal, 2024)
IgA vasculitis is rare in adult. A significant portion of adult cases may present with renal involvement. Although most of these cases can be managed symptomatically, some cases may require immunosuppressive treatment. Unless diagnosis and appropriate treatment is initiated early IgA nephropathy in adult may result in chronic kidney disease. Immunoglobulin A vasculitis (IgAV) is an acute disorder causing generalized vasculitis principally involving skin, gastrointestinal (GI) tract, kidneys and joints. Here, a 28 year old man was presented with purpuric rash with leg ulcer, inflammatory arthritis involving multiple joints, abdominal pain and vomiting. He had mild pedal edema and normal blood pressure. Investigations showed raised inflammatory markers, haematuria, and nephrotic range proteinuria with normal liver and renal function. Biochemical and immunological evaluation of lupus nephritis, ANCA associated vasculitis and other causes of glomerulonephritis were negative. Renal biopsy with direct immunofluorescence showed features of IgA nephropathy. Patient was treated with steroid and mycophenolate mofetil with a good response. Bangladesh Med J. 2022 Sept; 51(3): 47-50